A selective non-operative approach to thoracic stab wounds is safe and cost effective – a South African experience - Dayananda, KSS (Ann R Coll Surg Engl, 2018)
INTRODUCTION: Penetrating thoracic trauma is common and costly. Injuries are frequently and selectively amenable to non-operative management. Our selective approach to penetrating thoracic trauma is reviewed and the effectiveness of our clinical algorithms confirmed. Additionally, a basic cost analysis was undertaken to evaluate the financial impact of a selective nonoperative management approach to penetrating thoracic trauma. MATERIALS AND METHODS: The Pietermaritzburg Metropolitan Trauma Services electronic regional trauma registry hybrid electronic medical records were reviewed, highlighted all penetrating thoracic traumas. A micro-cost analysis estimated expenses for active observation, tube thoracostomy for isolated pneumothorax greater than 2 cm and tube thoracostomy for haemothorax. Routine thoracic computed tomography does not form part of these algorithms. RESULTS: Isolated thoracic stab wounds occurred in 589 patients. Eighty per cent (472 cases) were successfully managed nonoperatively. Micro-costing shows that active observation costs 4,370 ZAR (£270), tube thoracostomy for isolated pneumothorax costs 6,630 ZAR (£400) and tube thoracostomy for haemothorax costs 21,850 ZAR (£1,310). DISCUSSION: Penetrating thoracic trauma places a striking financial burden on our limited resources. Diligent and serial clinical assessments, alongside basic radiology and stringent management criteria, can accurately stratify patients to correct clinical algorithms. CONCLUSION: Selective nonoperative management for penetrating thoracic trauma is safe and effective. Routine thoracic computed tomography is unnecessary in all patients with isolated thoracic stab wounds, which can be reserved for a select group who are identifiable clinically. Routine thoracic computed tomography would not be financially prudent across Pietermaritzburg Metropolitan Trauma Services. Government action is required to reduce the overall incidence of such trauma to save resources and patients.